2016
DOI: 10.1016/j.expneurol.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dendritic morphology and neurotransmitter phenotype of thoracic descending propriospinal neurons after complete spinal cord transection and GDNF treatment

Abstract: After spinal cord injury (SCI), poor regeneration of damaged axons of the central nervous system (CNS) causes limited functional recovery. This limited spontaneous functional recovery has been attributed, to a large extent, to the plasticity of propriospinal neurons, especially the descending propriospinal neurons (dPSNs). Compared with the supraspinal counterparts, dPSNs have displayed significantly greater regenerative capacity, which can be further enhanced by glial cell line-derived neurotrophic factor (GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…92 The number of propriospinal neurons proximal to an SCI is severely depleted after a thoracic SCI, but short axon propriospinal neurons within the lumbosacral enlargement show no qualitative loss at 2 weeks. 118 We have demonstrated dendritic changes in propriospinal neurons after SCI, 119 and such changes could result in alterations in the activity of these neurons, leading to the atrophy we observed in lumbar motoneurons. Should such potential reductions in propriospinal neurons be prevented by hormonal treatment, the rescue of the major afferent source to motoneurons could underlie the beneficial effects of hormone treatment on motoneuron dendrities we have observed.…”
mentioning
confidence: 87%
“…92 The number of propriospinal neurons proximal to an SCI is severely depleted after a thoracic SCI, but short axon propriospinal neurons within the lumbosacral enlargement show no qualitative loss at 2 weeks. 118 We have demonstrated dendritic changes in propriospinal neurons after SCI, 119 and such changes could result in alterations in the activity of these neurons, leading to the atrophy we observed in lumbar motoneurons. Should such potential reductions in propriospinal neurons be prevented by hormonal treatment, the rescue of the major afferent source to motoneurons could underlie the beneficial effects of hormone treatment on motoneuron dendrities we have observed.…”
mentioning
confidence: 87%
“…Numerous evidences show that the dendritic spines can change shape, size, and number following various injuries (44,45). GV treatment also promotes synaptic plasticity via regulating CPLX1.…”
Section: Discussionmentioning
confidence: 99%
“…After SCI, there is an acute reduction in dendritic number in these survived neurons with rapid dendritic atrophy. Meanwhile, spontaneous dendritic plasticity could reflect a compensatory response of the spinal cord to the functional deficits caused by the injury (45,46) As yet, one of the important strategies for treating SCC is to promote axon regeneration in the epicenter (49). Data demonstrated that decreased CPLX1 expression promoted axon regrowth even when neurons were incubated in an inhibitory environment through highly up-regulation of GAP43 involving in axonal growth and regeneration (25,50).…”
Section: Discussionmentioning
confidence: 99%
“…GV also promotes synaptic plasticity via regulating CPLX1. Numerous evidences show that the dendritic spines can change shape, size, and number following various injuries (Tan&Waxman, 2012;Deng et al, 2016). After SCI, there is an acute reduction in dendritic number in these survived neurons with rapid dendritic atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…After SCI, there is an acute reduction in dendritic number in these survived neurons with rapid dendritic atrophy. Meanwhile, spontaneous dendritic plasticity could reflect a compensatory response of the spinal cord to the functional deficits caused by the injury (Horch et al, 2011;Deng et al, 2016). Increased dendritic spine density observed in neurons have entered into a more plastic state, which indicate availability to form new synapses (Alvarez&Sabatini, 2007).…”
Section: Discussionmentioning
confidence: 99%